Acetazolamide Improves Right Ventricular Function and Metabolic Gene Dysregulation in Experimental Pulmonary Arterial Hypertension - Spyropoulos, Fotios; Michael, Zoe; Finander, Benjamin; Vitali, Sally; Kosmas, Kosmas; Zymaris, Panagiotis; Kalish, Brian T.; Kourembanas, Stella; Christou, Helen (Frontiers in Cardiovascular Medicine, 2021)
Background: Right ventricular (RV) performance is a key determinant of mortality in pulmonary arterial hypertension (PAH). RV failure is characterized by metabolic dysregulation with unbalanced anaerobic glycolysis, oxidative phosphorylation, and fatty acid oxidation (FAO). We previously found that acetazolamide (ACTZ) treatment modulates the pulmonary inflammatory response and ameliorates experimental PAH. Objective: To evaluate the effect of ACTZ treatment on RV function and metabolic profile in experimental PAH. Design/Methods: In the Sugen 5416/hypoxia (SuHx) rat model of severe PAH, RV transcriptomic analysis was performed by RNA-seq, and top metabolic targets were validated by RT-PCR. We assessed the effect of therapeutic administration of ACTZ in the drinking water on hemodynamics by catheterization [right and left ventricular systolic pressure (RVSP and LVSP, respectively)] and echocardiography [pulmonary artery acceleration time (PAAT), RV wall thickness in diastole (RVWT), RV end-diastolic diameter (RVEDD), tricuspid annular plane systolic excursion (TAPSE)] and on RV hypertrophy (RVH) by Fulton's index (FI) and RV-to-body weight (BW) ratio (RV/BW). We also examined myocardial histopathology and expression of metabolic markers in RV tissues. Results: There was a distinct transcriptomic signature of RVH in the SuHx model of PAH, with significant downregulation of metabolic enzymes involved in fatty acid transport, beta oxidation, and glucose oxidation compared to controls. Treatment with ACTZ led to a pattern of gene expression suggestive of restored metabolic balance in the RV with significantly increased beta oxidation transcripts. In addition, the FAO transcription factor peroxisome proliferator-activated receptor gamma coactivator 1-alpha (Pgc-1α) was significantly downregulated in untreated SuHx rats compared to controls, and ACTZ treatment restored its expression levels. These metabolic changes were associated with amelioration of the hemodynamic and echocardiographic markers of RVH in the ACTZ-treated SuHx animals and attenuation of cardiomyocyte hypertrophy and RV fibrosis. Conclusion: Acetazolamide treatment prevents the development of PAH, RVH, and fibrosis in the SuHx rat model of severe PAH, improves RV function, and restores the RV metabolic profile.